My Memories of José Carlos Caracuel - Feliu, Jaume Cruz (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
I do not remember well the first time I spoke personally with José Carlos, but already in the late seventies we shared a number of common interests that made us have, academically, parallel lives. We were both radical behaviorists, who taught the subjects of Experimental Psychology, Theories of Learning (the current subject of Conditioning and Learning) and Human Learning. Our common interest in human learning led us to begin our respective theses - with the invaluable support of our common director, Professor Ramón Bayés - on the application of Experimental Behavioral Analysis to education. In a time of scarce bibliographical resources, we communicated by telephone the news we found and shared photocopied material by mail. Both theses took longer than expected and desirable, because we had started teaching several new subjects at the University of Seville, José Carlos, and at the Collegi Universitari de Girona, first, and then at the Universitat Autònoma de Barcelona, myself. Read More ...